Analisis Mutu Kinerja di SMA Negeri 1 Cilamaya - Agus Suryana; Qowaid Qowaid; Vina Fauziyah (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
This study aims to describe the quality of teacher performance at SMA Negeri Cilamaya. Performance analysis using SWOT technique. From the SWOT analysis activities at SMA Negeri 1 Cilamaya, it can be concluded that the formulation of strategic management at SMA Negeri 1 Cilamaya is in the good category. This can be seen in the results of the analysis, although it shows that SMA Negeri 1 Cilamaya is in quadrant II. This position signifies a strong organization but faces great challenges. The strategic recommendation given is Strategy Diversification, meaning that the organization is in a stable condition but faces a number of severe challenges, so it is estimated that the wheels of the organization will have difficulty continuing to spin if it only relies on the previous strategy. Therefore, organizations are advised to immediately increase their variety of tactical strategies. Keywords: quality, SWOT, Teacher performance